The Relationship between Internal Satisfaction and External Satisfaction amongst Hotel Customers in Malaysia - Yunus, Nek Kamal Yeop; Ishak, Salomawati (International Journal of Economics, Business and Management Studies, 2012)
This paper is focused on hotel customers’ internal and external satisfaction. Some previous studies had only focused on the customers’ external satisfaction and only a few studies had managed to link between the two variables. The study also looked into factors which may act as internal variables such as the employer-employee relationship, employee relationship as well as employee- customer relationship. As for the external variables, these may involve looking into other aspects of satisfaction, such as customer satisfaction towards the service and facilities provided by the hotel. The main focus of the study was to view the relationship between the customers’ intrinsic satisfaction with the customers’ external satisfaction and the factors which may influence the customers. The data had been randomly gathered from 120 samples by questionnaire distribution among hotel guests and employees in Kuala Lumpur, Port Dickson, Penang, Trengganu and Kota Kinabalu. Overall, this study had managed to uncover the factors which influenced customers’ internal and external satisfaction and also discovered possible relationship between the two types of satisfaction.